(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The foundational premise of mainstream intergenerational ethics, as articulated by thinkers like Hans Jonas and John Rawls, is that future generations will inherit a "natural" world—a biogeophysically stable Earth system broadly analogous to the Holocene conditions that nurtured the development of human civilization. The proposed epoch of the Anthropocene fundamentally shatters this premise. This paper argues that future generations will not inherit a pristine or self-regulating nature, but a planet pervasively and perpetually shaped by direct human technological management, from climate geoengineering and genetic rescue of species to large-scale pollution remediation and automated conservation systems. This seismic shift renders traditional models of intergenerational ethics, centered on conservation, non-maleficence, and resource distribution, critically inadequate. Our primary duty to the future is no longer merely one of preserving a natural legacy but has transformed into a daunting responsibility of stewardship over complex, irreversible socio-ecological-technological systems. This paper investigates the profound ethical implications of this new responsibility, which we term the "Anthropocene Inheritance." It entails novel and poorly understood obligations, including the duty to transmit the capacity and knowledge to manage these technological systems, the justice implications of imposing "obligatory technological dependencies," and the rights of future people to consent to or refuse their inherited technological condition. Through an analysis of emerging technologies like Solar Radiation Management and CRISPR-driven genetic conservation, this paper develops a new ethical framework: "Techno-Stewardship Justice." This framework obligates present generations to ensure that the actively managed planet we bequeath is not only habitable but also just, navigable, and does not foreclose the ability of future generations to define their own relationship with the world, thereby preserving their autonomy in a post-natural age.